Food Safety: Risks and Benefits of Eating GM Foods in Human Health/Segurança alimentar: riscos e benefícios da ingestão dos alimentos transgênicos na saúde humana - Larissa Emanuely Silva Nobre; Jenifer Mikaely Lima dos Santos; Raíssa Medeiros Maciel; Yasmin Lima Rodrigues; Silvânia Alves Ladeira; Matteus Freitas de Oliveira; Jackson Belo Pereira (Universidade Estadual de Alagoas, 2020)
The research discussed the impacts that transgenic foods bring to the population due to their positive and negative effects, as well as to study the supply of these foods between the global and local scales, with emphasis on the city of Batalha-Alagoas. The widespread use of viruses and bacteria with high recombinant potential can create new pathogenic strains and diseases that endanger human health. This research has the character of bibliographic prospecting, associated with the realization of a field stage that took place in the city markets. Associating these sources, maps and tables were produced to analyze the results. It has been noted that the supply and consumption of genetically modified food on a world scale is vast, as well as proportionally occurring on the local scale, causing people to consume more genetically modified food than organic food because of its practicality and your cost. Agribusiness actions have reduced the possibility of articulation of the peasantry that values the production of organic and pesticide-free foods and transgenics.